Plasma-derived industry and plasma-derived medicinal products in the Italian National Blood Transfusion Service. (October 2019) - De Silvestro, Giustina; Marson, Piero; Breda, Antonio; De Angelis, Vincenzo
Abstract: The priority objectives of the Italian Transfusion System are self-sufficiency for blood components and for plasma-derived products. Currently the collection activity guarantees self-sufficiency of blood components, including plasma for clinical use, but not for plasma-derived drugs, ie albumin and immunoglobulins in particular. The National Plasma Program of 2016–2020, issued a Ministerial Decree on December, 2, 2016, aims to achieve this goal, both by increasing the collection of plasma and therefore its transfer to plasma derivation companies, and by increasing the appropriateness of the requests. Currently, the companies Grifols SpA, Kedrion SpA, CSL Behring, and Baxter-Baxalta Srl are present on the Italian market, individually or in business associations, with which the various Italian regions have established an agreement based on the national legislation.